Final Cut Pro X. - Anderson, Andy ([Infinite Skills], 2011)
"In this video training course for Final Cut Pro X, expert author, teacher and chef Andy Anderson introduces you to this latest version of the popular video editing software from Apple. Whether you are a pro transitioning to FCP X, or a beginner who just wants to put together clips of your children, this video tutorial will teach you how to do that! Starting with the very basics - setting up your preferences. From there, you will cover topic like organizing and planning your projects, importing your source material, and setting up your project. You will then jump the heart of the matter - editing. Ripple edits, replace editing, three-point edits, even editing and managing your audio - you will learn it all. Andy then brings the fun with transitions, filters and matts. You will create titles, and add text and even animations to your video. A close look at color management leads to the most important - sharing your video, and a multitude of output options. By the conclusion of this computer based training course, you will be fully capable of importing, editing sprucing up and finally outputting all your video projects, from feature film to baby's first steps. This course includes extensive video and audio working files so that you can learn alongside the author with the same file he is showing in the training."--Resource description page.